Pengaruh Permainan Rangking Satu berbantuan Powerpoint Interaktif terhadap Hasil Belajar IPAS di Kelas IV SD - Fitria, Nur Diana; Khamdun, Khamdun; Bakhruddin, Ahmad (Jurnal Riset Madrasah Ibtidaiyah, 2024)
Monotonous learning in class IV at SDN Kropak 02 makes students less motivated, thus affecting their learning outcomes. Learning methods and media that motivate learning are deemed necessary because students who have high learning motivation can achieve high learning outcomes as well. Thus, this research aims to determine the magnitude of the influence of the first ranking game assisted by interactive PowerPoint on science learning outcomes in class IV at SDN Kropak 02. This research uses a quantitative pre-experimental design method with a one group pretest-posttest design. The research was conducted with 22 samples. Data was obtained from research instruments in the form of pretest and posttest questions on the science material. Data analysis used the paired sample t-tast test and n-gain test. After the pretest and posttest were carried out, the average of the social studies pretest was 43.64 and the science pretest was 42.73, while the average of the social studies posttest was 75.00 and the science posttest was 74.09. From the average value, the sig value is obtained. in the paired sample t-tast test 0.000. Then the n-gain test results obtained a mean n-gain score of 0.5792. From the results of the data analysis, it was concluded that the ranking one game method assisted by interactive PowerPoint had a significant influence on science and science learning outcomes in class IV at SDN Kropak 02. This method had a moderate level of influence or was quite effective for use in science and science learning for class IV at SDN Kropak 02.